The Contribution of Pondok Pesantren (Islamic Boarding School) to Developing Poor’s Mental Health - Prabowo, Hendro; Dewi, Mahargyantari Purwani; Firdaus, Mu'minatus; Afandi, Nur Azis; Marissa, Aski (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
Islamic boarding schools (pondok pesantren) play a role not only in education but also in the development of mental health. Pondok Tetirah Dzikir (PTD) is one of the pondok pesantren that provides mental health services for people experiencing poverty, especially those suffering from mental disorders and drug abuse, by using TQN-based therapy (Thariqah Qadiriyah Naqsabandiyah). This research is a case study and qualitative research on the development of mental health in PTD. Results show some themes, including the patients as a guest, management of the boarding schools, the therapeutic process and the social relationship after therapy, were found.